Sleep quality and trading behavior of individual investors on the stock market - Quang, Luu Thu; Vinh, Tran Tuan; Yen, Nguyen Dang Hai; Duong, Khoa Dang (Journal of Business Economics and Management, 2025)
There are various factors that influence the trading behavior of individual investors in the stock market. This study, based on data from 405 individual investors, is the first to investigate the relationship between sleep quality and investors’ trading behavior in the stock market. Sleep quality is assessed through factors such as sleep time, duration, number of awakenings during the night, and napping habits. By applying various regression methods (Logit, PCA, PLSR, GMM), the results show that increased sleep duration causes passive investors to hold fewer stocks in their portfolios during bull market years and to increase their holdings when the market declines. Conversely, for active investors, an increase of sleep duration prompts them to hold a greater number of stocks in their portfolios during bull market periods, and decrease their holdings during bear markets. Moreover, good sleep quality is correlated with improved investment performance for passive investors. Research also indicates that afternoon naps and nighttime sleep affect investors’ trading frequency. This study provides valuable insights into investors’ trading behavior in the stock market. We encourage investors to enhance the quality of their sleep and incorporate regular midday naps to remain mentally alert, ultimately leading to increased investment returns.